Efeito de reguladores de crescimento de insetos sobre populações de Aedes aegypti (DIPTERA: CULICIDAE), Paraíba, Brasil - Henriques, Alleksandra Dias da Silva (2014)
The diflubenzuron and novaluron are Insect Growth Regulators recommended by the World Health Organization (WHO) drinking water and have great potential for action on populations of Aedes aegypti use. The study aimed to establish the status of susceptibility of four natural populations of A. aegypti and determine the residual effects of these insecticides, as well as characterize the performance of diflubenzuron on larval stage of the insect and on the oviposition and egg viability of the vector. In the evaluation of susceptibility and residual activity were used as recommended by WHO for both products, 0.25 mg/l of diflubenzuron and 0.02 mg / l of novaluron doses. The effect of diflubenzuron on larval development was evaluated by subjecting first instar larvae (L1) of two populations of A. aegypti to five concentrations of the insecticide, 0.0025, 0.125, 0.025, 0.0375 and 0.05 mg/l for test the action of the product on the oviposition behavior, females were subjected to a multiple choice test, in which the dosages of 0.025 and 0.25 mg/l of the product and the eggs were used in this experiment were tested for viability. All populations showed high levels of inhibition of adult emergence (IE), 98.9 to 100% for IE, when submitted to diflubenzuron and novaluron. The diflubenzuron showed a residual activity of 12 weeks on two populations of A. aegypti and novaluron promoted 100 % of IE for 4 consecutive weeks in the same populations. Regarding the effect of diflubenzuron on larval development of A. aegypti, the first instar insect showed a shorter duration compared to L 2 and L 3 stages in all treatments of diflubenzuron and L 2 instar were recorded the highest average mortality compared to the other stages of larval development. As regards pesticide activity on oviposition and viability of eggs of A. aegypti, showed the occurrence of oviposition of A. aegypti in the solutions of diflubenzuron, as well as the viability of the eggs treated with the insecticide.